Economic Warfare and the Sea Grand Strategies for Maritime Powers, C. 1600-1945 - Morgan-Owen, David G. (Liverpool University Press, 2020)
Economic Warfare and the Sea examines the relationship between trade, maritime warfare, and strategic thought between the early modern period and the late-twentieth century. Using a variety of geographic and chronological examples, it presents a longue duree approach to a crucial theme in maritime strategic thought
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1650-1945; War-Economic aspects-History; Seemacht; Wirtschaft; Krieg; Seeschifffahrt; Konferenzschrift -- 2017 -- Oxford